Assessment of the Degree of Nominal Convergence of the Bulgarian Economy with the Economies of the European Union Member States in the Period 2017 – 2022 - Kaneva, Aglika (Research Papers, 2024)
In this paper, the degree of nominal convergence of the Bulgarian economy with the European economy has been assessed by analysing price stability, long-term interest rates, exchange rate stability and the government budget position. The main economic indicators for our country for the period 2017 – 2022 have been studied.